KHAMAR DALAM TINJAUAN AL-QURAN DAN ILMU KESEHATAN - Naffasa, Resya Farasy Fitrah (Hadharah: Jurnal Keislaman dan Peradaban, 2023)
The main topic in this article is khamr. Khamr is a drink made from ethanol, which is an addictive substance that can make the drinker addicted and cause poisoning or also called drunkenness. Mufassir agree that drinking khamar is haram, whether it is a drink made from fermented grapes or other. All kinds of intoxicating drinks are forbidden to be consumed. both in small and large quantities. Prohibition of consuming this drink because khamar has a negative impact on the body that is damaging the central nervous system. This is in accordance with research that has been done by doctors in the world of health.